KIDNEY FAILURE–CAUSES, SYMPTOMS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Kidney failure is a pathological condition that occurs in various diseases and is characterized by a violation of all kidney functions. In this case, water, electrolyte, nitrogen and other types of exchange are lost. Acute and chronic kidney failure are distinguished.